EFFECT ON THE FINANCIAL CONDITION AND PROFITABILITY OF NONFINANCIAL PERFOMANCE IN THE INDONESIAN SHIPPING COMPANY - Supardi Supardi (STIE Mandala Jember, 2018)
Abstract: One problem often encountered by management in the shipping industry companies in Indonesia are financial problems, because it collided with the availability of working capital which the company cannot be operated because the funds will be used for the purchase of raw materials and to give employees salary.This research analyzes the influence of financial condition consisting of working capital, asset structure, operating leverage, and sales growth on the firm profitability as well as on its non financial performance of ship building companies in Indonesia. By employing the multiple regression, the result of the estimation showed that among those variables underlined, working capital, asset structure, and sales growth proved to be significantly affecting the firm profitability and its nonfinancial performance, meanwhile the operating leverage has been proved non-significant. This research concludes that the management should pay more attention on working capital and the asset structure being the predominant variable, besides its asset structure and the sales growth, affecting the ship building companies performance in Indonesia. Shipping companies can grow and expand. To be able to increase profitability by increasing the shipping company's own capital and reducing a portion of the shipping company, the more active equity and profitability will also be good. On the other hand if it continues to rely on capital from outside, it will cause emergence of interest expense to be borne by the shipping company. Keyword: Working Capital, Asset Structure, Operating Leverage, Sales Growth, Profitability, Non-Financial Performance.